The Gastrointestinal disorders and leaky gut syndrome in endurance athletes - Izabela Murawiec; Magdalena Konert (Kazimierz Wielki University, 2023)
Gastrointestinal disorders are common in endurance-sport athletes, and can negatively affect physical performance and general health. During long lasting exercises such like ultramarathon, triathlon, marathon a characteristic phenomenon is the increase in the concentration many proinflammatory markers and proteins such like IL-1, IL-6, TNF-alfa, LPS, CK and C-reactive protein. Despite observed biochemical changes on of the typical "side effects" of physical activity is increased intestinal permeability, also called to as leaky gut. Recent research has demonstrated that even one hour of of intense endurance training note even with a maximum work capacity can lead to leaky gut symptoms and gastrointestinal disorders. Increased intestinal permeability is accomplished with changes of numerus molecular biomarkers, that indicate presence of this disease state and the degradation of the intestinal mucosa, such like lipopolysaccharides, zonulin, lactulose/rhamnose ratio, occludin and I-FABP, and many other. The understanding of this processes and understanding of the molecular mechanisms involved in the induction of leaky gut syndrome can lead to funding new methods and means of both avoiding and treating this condition.